'Soprattutto non ti abbandonare a monologhi svagati o maldicenti o rabbiosi': Traces of Simone de Beauvoir's 'Monologue' in Elena Ferrante's I giorni dell'abbandono. - Bounabat, Sarah Leïla (Italianist, 2025)
In its exploration of Olga's reaction to her husband's sudden departure with a younger woman, Elena Ferrante's I giorni dell'abbandono (2002) establishes a structural dialogical relationship with Simone de Beauvoir's La femme rompue (1967). The existing scholarship that examines Ferrante's intertextual engagement with Beauvoir's collection of short stories focuses on 'La femme rompue', its eponymous final story. However, Ferrante's novel also includes crucially significant references to 'Monologue', the second short story in Beauvoir's volume. I argue that extending the comparison between the two works to include 'Monologue' allows a more accurate understanding of the dialogue sustained in Ferrante's novel with Beauvoir's collection. In particular, I demonstrate how 'Monologue' informs Olga's recourse to monological and obscene forms of speech. I also scrutinize the process of fragmentation and reconstruction of Olga's interiority — an element that speaks to 'La femme rompue' but also to 'Monologue'.